Novel Pyrrole Derivatives as Multi-Target Agents for the Treatment of Alzheimer's Disease: Microwave-Assisted Synthesis, In Silico Studies and Biological Evaluation - Emilio Mateev; Valentin Karatchobanov; Marjano Dedja; Konstantinos Diamantakos; Alexandrina Mateeva; Muhammed Tilahun Muhammed; Ali Irfan; Magdalena Kondeva-Burdina; Iva Valkova; Maya Georgieva; Alexander Zlatkov (MDPI AG, 2024)
Considering the complex pathogenesis of Alzheimer's disease (AD), the multi-target ligand strategy is expected to provide superior effects for the treatment of the neurological disease compared to the classic single target strategy. Thus, one novel pyrrole-based hydrazide (vh0) and four corresponding hydrazide-hydrazones (vh1-4) were synthesized by applying highly efficient MW-assisted synthetic protocols. The synthetic pathway provided excellent yields and reduced reaction times under microwave conditions compared to conventional heating. The biological assays indicated that most of the novel pyrroles are selective MAO-B inhibitors with IC50 in the nanomolar range (665 nM) and moderate AChE inhibitors. The best dual-acting MAO-B/AChE inhibitor (IC50 hMAOB-0.665 μM; IC50 eeAChE-4.145 μM) was the unsubstituted pyrrole-based hydrazide (vh0). Importantly, none of the novel molecules displayed hMAOA-blocking capacities. The radical-scavenging properties of the compounds were examined using DPPH and ABTS in vitro tests. Notably, the hydrazide vh0 demonstrated the best antioxidant activities. In addition, in silico simulations using molecular docking and MM/GBSA, targeting the AChE (PDB ID: 4EY6) and MAO-B (PDB: 2V5Z), were utilized to obtain active conformations and to optimize the most prominent dual inhibitor (vh0). The ADME and in vitro PAMPA studies demonstrated that vh0 could cross the blood-brain barrier, and it poses good lead-like properties. Moreover, the optimized molecular structures and the frontier molecular orbitals were examined via DFT studies at 6-311G basis set in the ground state.